Localization of SV40 genes within supercoiled loop domains. - Nelkin, B D (1980)
Recent studies indicate that eukaryotic DNA is organized into supercoiled loop domains. These loops appear to be anchored at their bases to an insoluble nuclear skeleton or matrix. Most of the DNA in the loops can be released from the matrix by nuclease digestion; the residual DNA remaining with the nuclear matrix represents sequences at the base of the loops, and possibly other sequences which are intimately associated with the nuclear matrix for other reasons. Using a quantitative application of the Southern blotting technique, we have found this residual DNA from SV40 infected 3T3 cells to be enriched in SV40 sequences, indicating that they reside near matrix-DNA attachment points. An enrichment of 3-7 fold relative to total cellular DNA, was found in each of three different lines of SV40 infected 3T3 cells. Control experiments with globin genes showed no such enrichment in this residual matrix DNA. This sequence specificity suggests that the spatial organization of DNA sequences within loops may be related to the functionality of these sequences within the cell.